2019
DOI: 10.1136/bcr-2019-229228
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal fat stranding on CT: a red herring in a post-caesarean section woman with Ogilvie’s syndrome (OS)

Abstract: A 30-year-old woman was referred for a surgical review with abdominal pain and distension 2 days post-caesearean section. Abdominal X-ray showed dilated bowel loops. CT of her abdomen however showed fat stranding around a thickened appendix, suggesting a differential diagnosis of acute appendicitis on top of a postoperative ileus. Failure to respond to intravenous antibiotics led to an emergent surgical exploratory laparotomy, by which time the progressive caecal dilatation had led to patchy necrosis and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Of note, a 2019 case study demonstrated that even in the presence of CT imaging revealing grossly dilated loops of bowel without evidence of mechanical obstruction, the diagnosis of Ogilvie's syndrome can be missed [ 3 ]. In that case study there was concurrent CT evidence of appendiceal thickening and fat stranding leading to the presumed diagnosis and conservative management of acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, a 2019 case study demonstrated that even in the presence of CT imaging revealing grossly dilated loops of bowel without evidence of mechanical obstruction, the diagnosis of Ogilvie's syndrome can be missed [ 3 ]. In that case study there was concurrent CT evidence of appendiceal thickening and fat stranding leading to the presumed diagnosis and conservative management of acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…In that case study there was concurrent CT evidence of appendiceal thickening and fat stranding leading to the presumed diagnosis and conservative management of acute appendicitis. The patient's case was complicated by caecal necrosis requiring a right hemicolectomy [ 3 ]. This further highlights the need for increased awareness [ 4 ] of Ogilvie's syndrome and the importance of early diagnosis and management in decreasing morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation